Enabling Privacy Preservation Technique to Protect Sensitive Data with Access Control Mechanism Using Anonymity - Kasab, Barkha; Pottigar, Vinayak; Ubale, Swapnaja (International Journal of Computer Sciences and Engineering, 2015)
Access control mechanisms shield sensitive data from unauthorized users. On the other hand, when sensitive information is released and a Privacy Protection Mechanism (PPM) is not in set up, an authorized user can still compromise the privacy of a person leading to identity exposure. A PPM can use concealment and speculation of social information to anonymize and fulfill protection prerequisites here some algorithm i.e. k-anonymity and l-diversity used against identity as well as attribute disclosure. However, security is accomplished at the expense of exactness of authorized data or information. Paper describes an accuracy-constrained privacy-preserving access control model. Role based access control policies define selection predicates available to roles and it should be satisfy the k-anonymity or l-diversity. An extra limitation that should be fulfilled by the PPM is the imprecision headed for every choice predicate. However, the problem of satisfying the accuracy constraints used for multiple roles has not been studied before. In our formulation ,technique used heuristics for anonymity algorithms and also done experiments to show proposed approach satisfies imprecision bounds for more permissions and find has lower total imprecision than the earlier methods.